Exosome-delivered BMP-2 and polyaspartic acid promotes tendon bone healing in rotator cuff tear via Smad/RUNX2 signaling pathway. Issue 1 (1st January 2022) - Han, Lei; Liu, Hong; Fu, Huajun; Hu, Yugen; Fang, Weili; Liu, Junsheng
ABSTRACT: Rotator cuff tear is the main form of shoulder joint injury, which seriously affects shoulder joint function. This study aimed to clarify the function and mechanism of exosomes containing polylactic acid (PLA), polylactic acid copolymer and BMP-2 in tendon bone healing of rotator cuff tear. First, CD44 expression in bone marrow mesenchymal stem cells (BMSCs) and CD90 and CD44 in exosomes were analyzed by flow cytometry. Then, stability and targeting identification of exosome-delivered bone morphogenetic protein (BMP)-2 and PLA microcapsules were measured by transmission electron microscopy (TEM), DiO/DiI staining. Finally, tendon-bone repair after acute rotator cuff rupture in rabbits was established, and the function of BMP-2 exosomes for tendon bone healing in rotator cuff tear was evaluated by micro-CT, biomechanical determination and histochemical staining methods. The results showed that the exosomes of polyaspartic acid-polylactic acid-glycolic acid copolymer (PASP-PLGA) microcapsules were successfully established which showed good stability and targeting. The bone mineral density (BMD), tissue mineral density (TMD) and bone volume fraction (BV/TV) were higher, while the stiffness and the ultimate load strength of the tendon interface were enhanced under treatment with exosomes of PASP-PLGA microcapsules. Histochemical staining showed that exosomes of PASP-PLGA microcapsules promoted tendon and bone interface healing after rotator cuff injury. The tendon regeneration- and cartilage differentiation-related protein expressions were significantly upregulated under treatment with exosomes of PASP-PLGA microcapsules. In conclusion, exosome-delivered BMP-2 and PLA promoted tendon bone healing in rotator cuff tear via Smad/RUNX2 pathway. Our findings may provide a new insight for promoting tendon healing.